DOI: 10.31274/rtd-180813-16449
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effectiveness of implementing the science writing heuristic on student performance in general chemistry

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
4

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 72 publications
2
13
0
4
Order By: Relevance
“…ATBÖ yaklaşımının öğrencilere rehberlik eden boyutu yedi aşamadan oluşmaktadır. Aynı zamanda bu aşamalar, süreci daha anlaşılır hale getiren bir veya iki soru cümlesi içermektedir (Poock, 2005). Öğrenciler araştırma sorularına, oluşturdukları araştırma sorularına yanıt teşkil eden iddialarına ve iddialarını desteklemek amacıyla sundukları kanıtlara odaklanan bu aşamalardaki soruları yazılı olarak yanıtlarlar (Hand, Prain ve Wallace, 2002).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…ATBÖ yaklaşımının öğrencilere rehberlik eden boyutu yedi aşamadan oluşmaktadır. Aynı zamanda bu aşamalar, süreci daha anlaşılır hale getiren bir veya iki soru cümlesi içermektedir (Poock, 2005). Öğrenciler araştırma sorularına, oluşturdukları araştırma sorularına yanıt teşkil eden iddialarına ve iddialarını desteklemek amacıyla sundukları kanıtlara odaklanan bu aşamalardaki soruları yazılı olarak yanıtlarlar (Hand, Prain ve Wallace, 2002).…”
Section: Introductionunclassified
“…Öğrenciler araştırma sorularına, oluşturdukları araştırma sorularına yanıt teşkil eden iddialarına ve iddialarını desteklemek amacıyla sundukları kanıtlara odaklanan bu aşamalardaki soruları yazılı olarak yanıtlarlar (Hand, Prain ve Wallace, 2002). Bu aşamalar ve bu aşamaları anlaşılır hale getiren sorular aynı zamanda öğrencilerin laboratuvarda icra edeceği araştırmasorgulamaya dayalı aktivitelerin yansıtılabildiği bir deney laboratuar raporunun işlem basamaklarıdır (Poock, 2005). Öğrencilere yönelik olarak geliştirilen şablon Tablo 1'de verilmiştir (Keys ve diğerleri, 1999).…”
Section: Introductionunclassified
“…Some of his students have responded particularly favorably to seeing the writings of other students, also some student in his study think that In-class writing forces him/her to think more about what he/she am writing about, thus creating an improved understanding of it. Poock (2005) commented on the importance of writing in the study of chemistry:…”
Section: Writing As a Learning Toolmentioning
confidence: 99%
“…Similarly, Rosenthal (1987, p. 996) suggested that there "is no question that students majoring in chemistry, and perhaps other sciences as well, graduate with underdeveloped writing skills." Therefore, writing is required to address an insufficiency among chemistry students (Poock, 2005). While a handbook for teachers to promote writing in the chemistry curriculum was developed by Kovac and Sherwood (2001), several articles also have been published that describe the variety of ways writing has been integrated into the chemistry classroom (Gordon et al, 2001;Paulson, 2001;Shires, 1991).…”
Section: Writing As a Learning Toolmentioning
confidence: 99%
See 1 more Smart Citation